Giant true celiac artery aneurysm - Aljabri Badr (The Saudi Journal of Gastroenterology, 2009)
Celiac artery aneurysms are rare and usually asymptomatic. The management of these aneurysms is challenging, especially when they are large and involve the confluence of the trifurcation. We present here a case of a large celiac artery aneurysm involving its branches in a young woman. Preoperative investigations, intraoperative findings, and the operative procedure are also presented and discussed.